Design Aid of Semi-rigid Connections for Frame Analysis - Kishi, N.; Chen, Wai-Fah; Goto, Y.; Matsuoka, K.G. (Engineering Journal, 1993)
In this paper, a useful design aid for determining the values of the initial connection stiffness Rki, the ultimate moment capacity Mu, and the shape parameter n of a three-parameter power model describing the moment-rotation curve (M-qr) of semi-rigid connections with angles is prepared for its use in the practical design of flexibly jointed frames with angles. A set of nomographs allows the engineer to rapidly determine the M-qr curve for a given connection. Applying the design aid, numerical simulations on drift and column moment of a flexibly jointed frame with angles are illustrated.